The relation between motivational and behavioral cultural intelligence and the three dimensions of cross-cultural adjustment among Arabs working in the USA - Dagher, Grace K. (2010)
This study investigates the relation between two facets of cultural intelligence and the three dimensions of cross cultural adjustment. Participants were Arabs working in the United States of America for a period of six months to five years. Using factor analysis and correlation analysis, the results of this study provides empirical support for Cultural intelligence scale and provides a support to the majority of the hypothesized relations. Moreover the results of this study provide insights for managers and future research. For a number of years the number of businesses going internationally has increased. With the increase of international businesses, an increase of cross-cultural interaction at the different levels and aspects of our life around the world took place. Today’s society is more culturally diverse than ever (Ang, Van Dyne, & Koh, 2006), and as a consequence individuals at the beginning of the twenty-first century are faced with more challenges arising from cross-cultural encounters than they have ever been (Ying & Han, 2006). Issues related to cultural diversity are especially important for today’s workforce as it is more culturally diverse than it has ever been. The failure to interact successfully with others from different cultures is one of the main difficulties, challenges, and expenses facing organizations and individuals around the world (Ang et al., 2006; Shaffer, Harrison, Gregersen, Stewart, & Ferzandi, 2006).